Expression of EBV Encoded viral RNA 1, 2 and anti-inflammatory Cytokine (interleukin-10) in FFPE lymphoma specimens: a preliminary study for diagnostic implication in Pakistan - Qadri Ishtiaq; Sheikh Taimoor I (BMC, 2011)
Abstract Background Epstein Barr Virus (EBV) plays a significant role as a cofactor in the process of tumorigenesis and has consistently been associated with a variety of malignancies. EBV encoded RNAs (EBER1 and EBER2) are the most abundant viral transcripts in latently EBV-infected cells and their role in viral infection is still unclear. Formalin Fixed Paraffin Embedded (FFPE) tissues of surgically removed carcinoma biopsies are widely available form but have never been exploited for expressional studies previously in Pakistan. Immunohistochemistry (IHC) and in situ hybridization (ISH) in FFPE biopsy tissues remains the gold standard for proving EBV relationship in a histopathological lesion but their reagents associated limitations confines their reliability in some applications. Recently introduced targeted drug delivery systems induce viral lytic gene expression and therefore require more sensitive method to quantify viral as well as cellular gene expression. Methods Eight (8) lymphoma samples were screened to detect the EBV genome. Qualitative and quantitative expression of EBV Encoded RNAs (EBER1, EBER2) and anti-inflammatory cytokine (interleukin-10) in FFPE EBV positive lymphoma tissue samples were then analysed by using Reverse transcriptase Polymerase Chain Reaction (RT-PCR) and Real Time Polymerase Chain Reaction (qRT-PCR), respectively. Results In this study we have successfully quantified elevated expressional levels of both cellular and viral transcripts, namely EBER1, EBER2 and anti-inflammatory cytokine (IL-10) in the FFPE Burkitt's lymphoma (BL) specimens of Pakistani origin. Conclusions These results indicate that FFPE samples may retain viral as well as cellular RNA expression information at detectable level. To our knowledge, this is first study which represents elevated expressional levels of EBER1, EBER2 and IL-10 in FFPE tissue samples of Burkitt's lymphoma in Pakistan. These observations will potentially improve current lacunas in clinical as well as diagnostic practices in Pakistan and can be further exploited to develop new strategies for studying cellular and/or viral gene expression.